Attitude and awareness on importance of breastfeeding among childbearing women in a rapidly developing country - Vamegh, Motahareh H.; Karkout, Rami A.; Shihan, Hadeel A.; Kaouas, Mujtaba C. (International Journal of Research in Medical Sciences, 2019)
Background: Health authorities in United Arab Emirates passed a law giving all the mothers the right to breastfeed their children even during the working hours. The objective of this study is designed to explore the degree of awareness among mothers in childbearing period on breastfeeding importance and practices. Methods: A cross sectional explorative questionnaire-based survey included 400 mothers from multi health centres in 3 emirates of United Arab Emirates as follows: Abu Dhabi 100 samples, Dubai 100 samples and Sharjah 200 samples, who were in their childbearing period and had a minimum of one child during the study period between July 2016 and November 2016. Results: Total 54.5% of mothers were above 30 years of age. 48% were local and 52% were non-local. 80% were familiar with the advantages of breastfeeding. 84.8% believed that exclusive breastfeeding up to 6 months is important and 41% had breastfed their children exclusively. 76% had the skin-to-skin contact with their baby and 43.5% had started breastfeeding within the first hour after birth, of them, 10% had delivered by caesarean section. 82% were roaming in with their baby during hospital stay and 81% had practiced demand breastfeeding. 89.9% of mothers had received the support they needed for breastfeeding from hospital staff. 56% had not used pacifier during the hospital stay and 56% had used bottle-feeding. 55% of mothers were employed, 72% of them had the intention to continue exclusive breastfeeding for a minimum of 6-month period. Conclusions: Attitude and awareness on breastfeeding are encouraging. Educational efforts, workshops and public awareness should be enhanced and maximized.